PERAN GAMBAR DALAM PENYELESAIAN SOAL GEOMETRI - Nur Hidayatul Muzdalifah; Lailatul Mubarokah; Risdiana Chandra Dhewy (Program Studi Pendidikan Matematika STKIP PGRI Sidoarjo, 2022)
This study aims to determine whether there is a difference in the average student learning outcomes for verbal geometry class and visual geometry class in terms of mathematical representation ability. Quantitative is this type of research. The implementation is in the 2020/2021 academic year in class X majoring in TKJ SMK Darussalam Sidoarjo. The samples were from class X TKJ 1 and X TKJ 2. The results of data analysis showed that the normality assumption test could be met, but the homogeneity test showed that the data had heterogeneous variants, so data transformation was carried out. The results of retesting the assumption of homogeneity still have heterogeneous variants, so the solution does not use a comparative test of 2 independent samples but uses the Mann Whitney nonparametric test. The test results show that there is a difference in the average student learning outcomes for the verbal geometry class and the visual geometry class in terms of mathematical representation abilities. This is evidenced by the results of the Mann Whitney test with a p-value of 0.001 0.05. This difference can also be seen through the average result of the visual geometry test of 80.42 which is higher than the result of the verbal geometry test, which is 52.33.